2018
DOI: 10.1021/acs.joc.8b00233
|View full text |Cite
|
Sign up to set email alerts
|

Ir-Catalyzed Synthesis of Substituted Tribenzosilepins by Dehydrogenative C–H/Si–H Coupling

Abstract: The Ir-catalyzed intramolecular reaction of 2',6'-diaryl-2-(hydrosilyl)biphenyls gave substituted tribenzosilepins by direct dehydrogenative C-H/Si-H coupling. This is the first example of catalytic construction of the tribenzosilepin skeleton. Enantiomerically pure tribenzosilepin was prepared by optical resolution using chiral HPLC, and its inversion barrier was calculated by measurement of rate of racemization using the Eyring kinetic equation under heating conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…In 2018, Shibata group achieved the first example of catalytic construction of a tribenzosilepin skeleton via monohydrosilane‐mediated Ir‐catalyzed intramolecular C(sp 2 )−H dehydrogenative silylation (Scheme 16). [26] The reaction likely via rare eight‐membered metalacyclic states, followed by reductive elimination, giving substituted tribenzosilepin derivatives along with formation of a seven‐membered ring. Besides, the system exhibited good functional group tolerence, giving the desired targets in moderate to good yield.…”
Section: Monohydrosilane‐mediated C−h Silylationmentioning
confidence: 99%
“…In 2018, Shibata group achieved the first example of catalytic construction of a tribenzosilepin skeleton via monohydrosilane‐mediated Ir‐catalyzed intramolecular C(sp 2 )−H dehydrogenative silylation (Scheme 16). [26] The reaction likely via rare eight‐membered metalacyclic states, followed by reductive elimination, giving substituted tribenzosilepin derivatives along with formation of a seven‐membered ring. Besides, the system exhibited good functional group tolerence, giving the desired targets in moderate to good yield.…”
Section: Monohydrosilane‐mediated C−h Silylationmentioning
confidence: 99%
“…6 The boat conformation of the sila-2,4,6-heptatriene ring is also evident from several X-ray crystallographic studies. [6][7][8][9][10][11][12][13] Simple, non-annulated silepins are relatively rare and only a limited number of examples are known. A tentatively assigned, fully substituted silepin was discussed at an early stage as a possible product from decomposition of a 7-silanorbornadiene derivative.…”
Section: Silepinsmentioning
confidence: 99%
“…With a substrate bearing two meta-substituted benzene rings, the cyclization proceeded efficiently and selectively at the less hindered site, while a substrate featuring a central naphthalene core gave a respectable yield of the product 41. 11 In this context, it should be noted that the closely related system 9,9-dimethyl-9H-tribenzo[b,d,f]silepin has been reported long time ago as a minor product from the reaction of 1,2-dichlorobenzene with chloromethoxydimethylsilane and sodium in refluxing toluene, 41 and a few years later also in very low yield (3.5%) from a dilithiated terphenyl derivative and dichlorodimethylsilane. 6 The silane 42, which is readily available by metalation of 3-bromoanisole with butyllithium and subsequent quench with dichlorodimethylsilane, constituted a starting point in an approach to fused silepins.…”
Section: © Author(s)mentioning
confidence: 99%
“…It is a surprise to see that the research on fluorescent silepins falls far behind that on borepins, even though the former are more stable and many potential candidates have been synthesized through intramolecular McMurry coupling, 29 ring-closing metathesis, 5a,30 and C-H/Si-H coupling, 31 even being utilized to synthesize borepin. The first photophysical and electrochemical study with blue fluorescent dibenzo[b,f]silepin (DBSi) was reported by Piers et al 11a The desired DBSi was synthesized from the same dibromo-reagent for DBB, but through a direct reaction of the resulting dilithium reagent with dichlorosilane.…”
Section: Scheme 12 Sequential Photoisomerization Of 54 and Reversiblementioning
confidence: 99%